Incidence and spread pattern of lymph node metastasis from submandibular gland cancer - Tamagawa, Kotaro; Otsuki, Naoki; Shimoda, Hikari; Morita, Naruhiko; Furukawa, Tatsuya; Teshima, Masanori; Shinomiya, Hirotaka; Nibu, Ken-ichi (European archives of oto-rhino-laryngology, 2023)
Objectives To clarify the indication of neck dissection (ND) for patient with submandibular gland (SMG) cancer. Methods A total of 43 patients with SMG cancer were retrospectively analyzed. Forty-one patients underwent ND: Levels I–V in 19 patients, Levels I–III in 18 patients, and Level Ib in 4 patients. The other two patients did not undergo ND, since preoperative diagnoses were benign. Postoperative radiotherapy was performed in 19 patients with positive surgical margin, high grade cancer or stage IV disease. Results LN metastases were pathologically confirmed in all patients with cN + and 6 out of 31 patients with cN–. No patients developed regional recurrence during follow-up periods. Ultimately, LN metastases were pathologically confirmed in 17 of 27 high grade, one out of 9 intermediate grade, but not in 7 low grade. Conclusions Prophylactic neck dissection should be considered in T3/4 and high grade SMG cancers.